A Case of Placental Mesenchymal Dysplasia. (20th November 2013) - Taga, Shigeki; Haraga, Junko; Sawada, Mari; Nagai, Aya; Yamamoto, Dan; Hayase, Ryoji
Abstract : Placental mesenchymal dysplasia (PMD) rarely complicates with pregnancy. A 30-year-old woman, gravida 3, para 3, presenting with placentomegaly, was referred to our department at 18 weeks of gestation. An ultrasonography revealed a normal fetus with a large multicystic placenta, measuring 125 × 42 × 80 mm. The border between the lesion and normal region was not clear. Color doppler revealed little blood flow in the lesion. Magnetic resonance imaging revealed normal fetus and a large multicystic placenta. Serum human chorionic gonadotropin level was 20124.97 U/L, which was normal at 20 weeks of gestation. Thus, placental mesenchymal dysplasia rather than hydatidiform mole with coexistent fetus was suspected. Then, routine checkup was continued. Because she had the history of Cesarean section, an elective Cesarean section was performed at 37 weeks of gestation, and 2520 g female infant with apgar score 8/9 was delivered. The baby was normal with no evidence of Beckwith-Wiedemann syndrome. Placenta of 20 × 16 × 2 cm, weighing 720 g, was bulky with grape like vesicles involving whole placenta. Microscopic examination revealed dilated villi and vessels with thick wall which was lacking trophoblast proliferation. Large hydropic stem villi with myxomatous struma and cistern formation were seen. PMD was histopathologically confirmed.